Analysis Study of Oriented Area Development Plan in Sukaresmi Area (Case Study: Sukaresmi Bogor, West Java Province) - Hidayah, Khoiron; Murtedjo, Tedy; Rulhendri, Rulhendri; Chayati, Nurul (ASTONJADRO, 2023)
Several cities in Indonesia have implemented a Transit Oriented Zone system in integrating a sustainable transportation system, the area at the Sukaresmi point has become one of the areas developed with the Transit Oriented Development (TOD) concept in the Presidential Regulation of the Republic of Indonesia Number 55 of 2018 concerning the Plan Main Transportation Jakarta, Bogor, Depok Tangerang and Bekasi in 2018-2029. The development of this area will generate new movements in the surrounding road network. Of course, it will have a negative impact on the surrounding traffic. The negative impacts include an increase in the volume of traffic flow which can cause congestion, pollution, accidents, and other things that cannot be avoided on roads in the area where there is no traffic management arrangement around the area, it is necessary to conduct a study on traffic impact analysis. and analysis of generation and pull, the performance of roads in the operation stage in 2024, the development of the sukaresmi area has a total of 37.316 m2. With traffic engineering to minimize congestion due to area development plans. From the analysis result, the basic building coefficient is 70%, the building floor coefficient is 4.98. In the existing conditions, the highway has a saturation level of > 1. The generation and pull that occurs is 1240 cur / hour. Whereas the operation stage, the road saturation level becomes> 1.Recommendations given are the provision of safe public transportation facilities, realizing the importance of road traffic and road transportation and a study of land ownership around the Sukaresmi-oriented development plan is needed.